Modeling Chronic Traumatic Encephalopathy: The Way Forward for Future Discovery - Turner, Ryan C.; Lucke-Wold, Brandon P.; Logsdon, Aric F.; Robson, Matthew J.; Lee, John M.; Bailes, Julian E.; Dashnaw, Matthew L.; Huber, Jason D.; Petraglia, Anthony L.; Rosen, Charles L. (Frontiers in Neurology, 2015)
Despite the extensive media coverage associated with the diagnosis of chronic traumatic encephalopathy (CTE), our fundamental understanding of the disease pathophysiology remains in its infancy. Only recently have scientific laboratories and personnel begun to explore CTE pathophysiology through the use of preclinical models of neurotrauma. Some studies have shown the ability to recapitulate some aspects of CTE in rodent models, through the use of various neuropathologic, biochemical, and/or behavioral assays. Many questions related to CTE development however remain unanswered. These include the role of impact severity, the time interval between impacts, the age at which impacts occur, and the total number of impacts sustained. Other important variables such as the location of impacts, character of impacts, and effect of environment/lifestyle and genetics also warrant further study. In this work we attempt to address some of these questions by exploring work previously completed using single and repetitive injury paradigms. Despite some models producing some deficits similar to CTE symptoms, it is clear that further studies are required to understand the development of neuropathological and neurobehavioral features consistent with CTE-like features in rodents. Specifically, acute and chronic studies are needed that characterize the development of tau-based pathology.